Vasculitis manifested with multiple mass lesions in kidneys, lungs and soft tissue, mimicking malignant tumors - Shunhua Guo, MD; Mary Ann R. Domingo, MD; Qin Chang, MD, PhD; Jordan K. Swensson, MD (Elsevier, 2019)
We report a case of granulomatosis with polyangiitis (GPA) (Wegner's granulomatosis) who presented with multiple mass lesions in kidneys and lung lobes, as well as neck soft tissue, mimicking malignancies. This 71-year-old woman initially presented with sudden right foot drop, left calf pain and right eye vision loss. She was treated with corticosteroid for the diagnosis of possible temporal arteritis. Months after steroid was tapered to 2 mg per day, she developed increasing fatigue, weight loss, and shortness of breath. CT scan showed lung mass lesions in left upper lobe (3.8 × 2.4 cm), right mid lung with pleural extension (3.4 × 3.3 cm), and right lower lobe (1.1 × 1.0 cm); right neck (3.3 × 2.6 cm), right kidney (2.3 × 1.8 cm) and left kidney (2.0 × 1.6 cm). Right quadriceps muscle biopsy shows focal granulomatous inflammation. Lung biopsy showed necrotizing and poorly formed granulomatous inflammation. Biopsies of kidney mass lesions showed necrotizing and non-necrotizing granulomatous inflammation. No crescentic or necrotizing glomerular lesions were observed in the total 40 sampled glomeruli. No malignancy was identified in any of the biopsies. Her c-ANCA was found to be positive and PR3-ANCA antibody was 6.88 U/ml (normal 0-0.90 U/ml). She was diagnosed with granulomatosis with polyangiitis and treated with high dose corticosteroid and rituximab. Eight months later, follow-up showed resolved mass lesions by chest X-ray and CT and stable renal function. The case highlights the atypical clinical presentation of vasculitis and the significance of considering this possibility in differential diagnosis when confronting mass lesions present in multiple organ systems. Biopsy is critical for the correct diagnosis to initiate timely and appropriate treatment, and also important to avoid unnecessary surgical resection. Keywords: Granulomatosis with polyangiitis, Wegner's granulomatosis, Anti-neutrophilic cytoplasmic antibody, ANCA, Mass, Vasculitis